The Interplay of the United States and the Muslim World in the Israel-Palestine Conflict: A Complex Web of Interests and Tensions - Farooq, Muhammad Arslan; Mumtaz, Sapna (Annals of Human and Social Sciences, 2024)
The main aim of this paper is examining the Israel Palestine conflict while focusing on the conlict of interests between the US and the Muslim World. This research delves into the complex interplay between these actors, analyzing the historical, political, and ideological factors that have shaped their relationships. The Israel-Palestine conflict represents a deeply entangled geopolitical web, with the United States and the Muslim world occupying pivotal positions. By employing qualitative case study approach, this research explores the intricacies of the US-Muslim world relationship in the context of the Israel-Palestine conflict, examining the impact of US foreign policy on regional stability, the role of religion and identity in shaping perceptions, and the potential avenues for conflict resolution. This study suggests that the US, as a staunch ally of Israel, has consistently supported its security and territorial claims, often at the expense of Palestinian interests. This stance has fostered resentment within the Muslim world, fueling anti-American sentiment and fueling support for Palestinian resistance movements. Moreover, the US has sought to maintain its regional influence and secure access to crucial energy resources, further complicating its role in the conflict. Moving forward, the US needs to adopt a more balanced approach that takes into account the concerns of both Israelis and Palestinians, as well as the Muslim world. This necessitates fostering a dialogue based on mutual respect and understanding, promoting a two-state solution, and ensuring equal rights and opportunities for both Palestinians and Israelis.